Relationship between EPSPS copy number, expression, and level of resistance to glyphosate in common waterhemp (Amaranthus rudis) from Kansas - Dillon, Andrew James (Kansas State University, 2015)
Common waterhemp (Amaranthus rudis) is a problematic weed species of cropping systems throughout the Midwestern states, including Kansas. Recently, waterhemp populations from Kansas were found to have evolved resistance to the widely used herbicide glyphosate as a result of amplification of the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), the enzyme target of glyphosate. The objectives of this research were to 1) perform glyphosate dose-response study and determine the relationship between relative EPSPS genomic copies and EPSPS gene expression in glyphosate-resistant waterhemp, and 2) characterize the genomic configuration and distribution of EPSPS copies using florescence in situ hybridization (FISH) in three glyphosate-resistant waterhemp populations. Waterhemp populations from eastern Kansas were screened with 868 g ae haˉ¹ (field used rate) of glyphosate, and genomic DNA and total RNA was isolated from the survivors to determine the EPSPS genomic copies and EPSPS gene expression relative to the acetolactate synthase (ALS) gene using qPCR. Furthermore, waterhemp specific EPSPS probes were synthesized to perform florescence in situ hybridization (FISH) on these glyphosate-resistant plants. Results of these experiments indicate a positive correlation between level of glyphosate resistance, EPSPS copies, and their expression. As expected, a negative correlation was found between shikimate accumulation and EPSPS copies. Sequencing of the EPSPS gene showed no presence of the proline 106 mutation, which is known to be associated with glyphosate resistance suggesting that an insensitive EPSPS enzyme was not involved in the mechanism of glyphosate resistance. FISH analysis of resistant plants illustrated presence of amplified EPSPS copies on two homologous chromosomes, likely near the centromeric region. . This is the first report demonstrating a positive relationship between EPSPS copies and expressions, as well as chromosome configuration of EPSPS copies in glyphosate- resistant waterhemp from Kansas.
Keywords: Common waterhemp; Glyphosate; Glyphosate resistance; Gene amplification; Agriculture, General (0473); Agronomy (0285); Biology, Plant Physiology (0817)